PERILAKU KONSUMEN DAN PENGAMBILAN KEPUTUSAN PEMBELIAN - AMIRULLAH - (STIE Indonesia Malang, 2022)
The purpose of this study is to describe consumer behavior in relation to purchasing decisions. Consumer behavior consists of the activities people perform when choosing what to buy and using products to satisfy needs and wants. The research was conducted through literature study to find references and literature on the topics covered. This study begins by describing the importance of understanding consumer behavior, the relationship of consumer behavior to marketing elements, and finally explaining the buying decision process. The consumer purchasing decision-making process is structured in five processes, namely: understanding the existence of a problem, searching for alternative solutions to problems, evaluating alternatives, purchasing or selecting, and post-purchase use and re-evaluation of the chosen alternative. demonstrated by its ability to influence and change consumer activities to achieve what is the target of the marketing strategy Keywords: consumer behavior, purchasing decisions, marketing management